Retrograde gastroesophageal intussusception: an exceedingly rare complication of Heller myotomy in a patient with achalasia cardia - Ishan Kumar; Richa Singh Chauhan; Ashish Verma (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kumar I, Chauhan RS, Verma A. Retrograde gastroesophageal intussusception: an exceedingly rare complication of Heller myotomy in a patient with achalasia cardia. Turk J Gastroenterol 2017; 28: 316-8.